Water Cannot Activate Traps of the Carnivorous Sundew Plant Drosera capensis: On the Trail of Darwin's 150-Years-Old Mystery - Pavlovič, Andrej; Vrobel, Ondřej; Tarkowski, Petr (Plants (Basel, Switzerland), 2023)
In his famous book Insectivorous plants, Charles Darwin observed that the bending response of tentacles in the carnivorous sundew plant Drosera rotundifolia was not triggered by a drop of water, but rather the application of many dissolved chemicals or mechanical stimulation. In this study, we tried to reveal this 150-years-old mystery using methods not available in his time. We measured electrical signals, phytohormone tissue level, enzyme activities and an abundance of digestive enzyme aspartic protease droserasin in response to different stimuli (water drop, ammonia, mechanostimulation, chitin, insect prey) in Cape sundew (Drosera capensis). Drops of water induced the lowest number of action potentials (APs) in the tentacle head, and accumulation of jasmonates in the trap was not significantly different from control plants. On the other hand, all other stimuli significantly increased jasmonate accumulation; the highest was found after the application of insect prey. Drops of water also did not induce proteolytic activity and an abundance of aspartic protease droserasin in contrast to other stimuli. We found that the tentacles of sundew plants are not responsive to water drops due to an inactive jasmonic acid signalling pathway, important for the induction of significant digestive enzyme activities.
Keywords: aspartic protease; carnivorous plant; digestive enzyme; sundew; jasmonic acid; abscisic acid